PENGEMBANGAN MODEL UNTUK MENINGKATKAN KUALITAS GURU MELALUI PELATIHAN LESSON STUDY DI SEKOLAH DASAR - Tjipto Subadi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
The purposes of the research study was to examine and identify a problem of the Primary Schools' teachers of Surakarta Residency in developing a model for improving a quality through lesson study training, a conceptual model for improving the Primary School teachers' quality through lesson study training, and model validation for improving the Primary School teachers' quality through lesson study theoretically. The research used an approach of descriptive-qualitative phenomenology by using a social definition. It was included in the class action. The subjects were the Primary School teachers of Surakarta. The informants of this study were the teachers, headmasters, and supervisors. The data gathering employed questionnaires, interview, and observation. The data analysis used the first order understanding and second order understanding with an interactive model, including data reduction, data display, and conclusion/ verification. The findings showed that a problem of the Primary School teachers is internal (teachers) and external (students, headmasters, supervisors, curriculum and facilities). The problem ranges from the most difficult (17.28%), the more difficult (30.88%), the difficult (33.99%) to the least difficult/easiest (17.85%). The lesson study conceptual model is based on a modified action class research. The effective and creative learning technique used the Improvement Model of Quality of Cooperative. The model validation employed an academic-administrative, conceptual, learning action, and professional.